Intraband hot-electron photoluminescence of a silver nanowire-coupled gold film via high-order gap plasmons. Issue 25 (18th June 2021) - Zhu, Xupeng; Shi, Huimin; Zhang, Shi; Yang, Zhengmei; Liao, Jun; Quan, Jun; Xue, Shuwen; Zou, Changwei; Zhang, Jun; Duan, Huigao
Abstract : High-order gap plasmon modes also support high-efficiency one-photon photoluminescence. Abstract : We report a strong one-photon photoluminescence (PL) behavior of a silver nanowire directly coupled gold film. The PL peak position of the silver nanowire-coupled gold film deviates from the intrinsic interband transition of gold materials and is not sensitive to the diameter change of the silver nanowire. We attribute this strong PL behavior to the intraband transition of hot electrons dominated by high-order gap plasmons, which are excited in the ultra-small gap formed by an ultra-thin polyvinyl pyrrolidone (PVP) layer coated on the silver nanowire. The results show that the energy required for the strong PL of the heterogeneous system mainly comes from the gold film, acting as an incident energy absorber enhanced by the high-order gap plasmons, while the silver nanowire acts an efficient incident energy focusing antenna. In situ Raman scattering spectra and time-resolved PL intensity integral curves were used to record the carbonization and disappearance process of PVP. The understanding of the PL behavior of the silver nanowire directly coupled gold film proves the universality of plasmon-modulated PL theory and is also of great significance to improve the generation and utilization efficiency of hot electrons with high-order gap plasmons in the fields of catalysis and incident energy capture.